FINANCIAL INNOVATION IN THE DIGITAL ECONOMY - Akhunova Shokhista Namanzhanovna; Tuichieva Shokhsanam (International Journal on Orange Technologies, 2021)
Financial innovations, financial and digital technologies transform the way of life, work, consumption, production of goods and services. In an increasingly competitive environment, the Internet offers opportunities to improve business and benefit from lower production costs. Using information and communication technologies (ICTs), small and medium-sized enterprises (SMEs) gain access to global markets that were once the prerogative of only large corporations. Digital platforms are changing the economics of doing business, reducing the cost of international interactions and transactions.